2020
DOI: 10.3390/ma13030699
|View full text |Cite
|
Sign up to set email alerts
|

Axial Displacements and Removal Torque Changes of Five Different Implant-Abutment Connections under Static Vertical Loading

Abstract: The aim of this study was to examine the settling of abutments into implants and the removal torque value under static loading. Five different implant-abutment connections were selected (Ext: external butt joint + two-piece abutment; Int-H2: internal hexagon + two-piece abutment; Int-H1: internal hexagon + one-piece abutment; Int-O2: internal octagon + two-piece abutment; Int-O1: internal octagon + one-piece abutment). Ten implant-abutment assemblies were loaded vertically downward with a 700 N load cell at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…Five studies (Cashman et al (2011), Ferreira et al (2012), Bernardes et al (2014), Al-Otaibi et al (2017), Kim et al (2020)) [ 20 , 35 , 36 , 42 , 47 ] have investigated the mechanical behavior of different connections as a function of time and tightening and untightening sequences. The studies were designed to test if multiple tightening and untightening sequences of abutment screws influenced the loss of preload.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies (Cashman et al (2011), Ferreira et al (2012), Bernardes et al (2014), Al-Otaibi et al (2017), Kim et al (2020)) [ 20 , 35 , 36 , 42 , 47 ] have investigated the mechanical behavior of different connections as a function of time and tightening and untightening sequences. The studies were designed to test if multiple tightening and untightening sequences of abutment screws influenced the loss of preload.…”
Section: Resultsmentioning
confidence: 99%
“…Even though this digital method can overcome the challenge of occlusal changes in the initial period after the delivery of restorations, a reliable connection between the implant and abutment should be confirmed to decrease the axial displacement of the abutment under functional loading [10,12,26]. The implant screw must be tightened with adequate torque to achieve the optimum preload [12,27,28]. In the present study, the abutment screw was retightened when the interim restoration was removed for taking the second impression, three months after the abutment connection.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, compressive force by long-term occlusal loading could generate plastic deformation of the interface of connection [11]. This settling phenomenon induces the axial displacement of the prosthesis [12]. The amount of settling of abutments to implants varies in all implant systems, and it has been reported that the implants with internal conical connection have higher settling values than those with external hexagonal connection [9,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 25 ] recommended increasing the torque value to above 30 Ncm to reduce screw loosening, stating that the torque value should be more than the value recommended by the manufacturer. Kim KS and Lim YJ[ 48 ] studied the abutment settling into the implants and the torque value removal under static loading. They concluded that loss of preload due to the settling effect can lead to screw loosening.…”
Section: Factors Affecting Abutment Screw Looseningmentioning
confidence: 99%